Vitrification Effects on the Transcriptome of in vivo-Derived Porcine Morulae - Cuello, Cristina; Martinez, Cristina A.; Cambra, Josep M.; González-Plaza, Alejandro; Parrilla, Inmaculada; Rodriguez-Martinez, Heriberto; Gil, Maria A.; Martinez, Emilio A. (Frontiers in Veterinary Science, 2021)
Despite the reported promising farrowing rates after non-surgical and surgical transfers of vitrified in vivo derived porcine morulae and blastocysts (range: 70-75%), the pregnancy loss is 5-15 fold higher with vitrified than with fresh embryos. The aim of the present study was to investigate whether vitrification affects the transcriptome of porcine morulae, using microarrays and qRT-PCR validation. Morulae were collected from weaned sows (n=13) by laparotomy on day 6 (day 0=estrus onset). A total of 60 morulae were vitrified (treatment group). After one week of storage, the vitrified morulae were warmed and cultured for 24 h in vitro. Non-vitrified fresh morulae (n=40) cultured for 24 h in vitro served as controls. After in vitro culture, embryo survival was assessed morphologically by stereomicroscopy. A total of 30 vitrified/warmed embryos that were deemed viable and 30 fresh control embryos (three pools of 10 for each experimental group) were selected for microarray analysis. A fold-change cut-off of ±1.5 and a p-unadjusted 0.05 were used to detect differentially expressed genes (DEGs). The survival rate of vitrified/warmed morulae (92.0 ± 8.3%) was similar to that of the control (100%). A total of 233 DEGs were identified in vitrified morulae (38 upregulated and 195 downregulated), compared to the control group. The impact of vitrification on the transcriptome of morulae can be considered moderate, considering the fold-change values, the number of significantly altered KEGG pathways and the percentage of altered genes in these pathways. Nine pathways were significantly modified. The disruption of metabolic pathways in morulae could be related to impaired embryo quality and developmental potential, despite the relatively high survival rates after warming observed in vitro. In conclusion, vitrification modified the gene expression pattern of in vivo-derived porcine morulae, resulting in moderate changes in the transcriptome that may interfere with subsequent embryo development and pregnancy after embryo transfer.